Global magnetization models with a priori information - Purucker, M.E.; Langel, R.A.; Rajaram, M.; Raymond, Carol (My University, 1998)
In an effort to explore the possible effects of change in integrated magnetization at the continent-ocean boundary and to account for such effects in modeling, an inverse technique is developed which allows for the inclusion of a priori information in models of global crustal magnetization or susceptibility. This technique accounts for processing effects such as main and external field removal. An a priori model consisting of an ocean-continent magnetic contrast, oceanic topography, and remanent magnetization in the Cretaceous quiet zones is constructed using equivalent source dipoles. Previous investigations using similar models utilize only forward modeling procedures. We show how this a priori model can be modified so that the resulting computed field, after removal of spherical harmonics below some specified degree (“main field” removal) and along track filtering (“external field” removal), matches that of the robust POGO-Magsat anomaly map in a least squares sense. The dependence of the final model on the a priori information is also investigated. Between degrees 20 and 60 the final models are found to be almost identical for reasonable a priori conditions. An example from the Gulf of Mexico and surrounding Gulf Coast region serves to illustrate the utility of the technique. High heat flow,>40° C/km, is observed in much of the Gulf Coast region. The example suggests that the elevated heat flow persists at depth and has elevated the Curie point.
Keywords: Gulf coast; Curie point; Ocean-continent magnetic contrast; Magnetization models